The Influence of Financial Performance on Company Value Through Dividend Policy as an Intervening Variable at BEI 2017-2022 - Meita Ratna Saomi; Hendro Sasongko; Herdiyana Herdiyana (International Forum of Researchers and Lecturers, 2025)
The purpose of this study is to determine and analyze the influence of financial performance on firm value with dividend policy as an intervening variable in manufacturing companies listed on the IDX for the period 2017-2022. This research uses a quantitative method with secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2022. The sampling method used is purposive sampling, with data from the last 6 years from 28 manufacturing companies listed on the IDX during 2017-2022. The data analysis techniques used are descriptive statistical analysis, panel data regression models, and path analysis. The results of the study show significant variations in liquidity, solvency, profitability, dividend policy, and firm value among manufacturing companies listed on the IDX during 2017-2022. Liquidity and profitability show large variations, reflecting differences in financial management and performance, solvency is more stable with low debt levels. Dividend policy and firm value show large variations, reflecting differences in profit sharing strategies and market valuation. Liquidity (cash ratio) has a positive effect on dividend policy (DPR), solvency (DER) has a positive effect on dividend policy, profitability (ROE) has a positive effect on dividend policy (DPR), liquidity (cash ratio) has a positive effect on firm value (PBV), solvency (DER) has a positive effect on firm value (PBV), profitability (ROE) has a positive effect on firm value (PBV), dividend policy (DPR) has a positive effect on firm value (PBV), liquidity (cash ratio) is unable to mediate through dividend policy (DPR) on firm value (PBV), solvency (DER) is unable to mediate through dividend policy (DPR) on firm value (PBV), profitability (ROE) is unable to mediate through dividend policy (DPR). on firm value (PBV)